Antioxidant Effect of Natural Honeys Affected by Their Source and Origin - Mellen Martin; Fikselová Martina; Mendelová Andrea; Haščík Peter (Polish Journal of Food and Nutrition Sciences)
In purpose to examine the antioxidant activity of 15 natural honeys of different origin ABTS method was used, total phenol content and dry matter content of honey samples were determined. Honeys were collected from different locations of Slovakia, Poland and Serbia and were represented as monofloral and multifloral samples (10) which originated from Poland and Slovakia, forest samples (4) originated from Serbia and honeydew honey. Average values of antioxidant activity observed in samples of honeys ranged from 0.62 to 4.63 mmol/kg. The highest antioxidant activity was detected in buckwheat honey and the lowest was shown in acacia honey. By observing the impact of individual honey samples on antioxidant activity it was found that the sample had a highly statistically significant effect. 10 homogeneous groups which varied in the antioxidant activity among each other were established by all 15 samples. Antioxidant activity of honeys could be a positive influence factor in terms of honey differentiation, especially in the case of the forest honeys collected from different places. Monofloral and multifloral honeys (10) established 5 homogenous groups, but in the case of several multifloral honeys which originated from different places of Poland and Slovakia no statistically significant differences were found.